Continual improvement needs of a library in a state university - Medrano, Virginia B. (Saint Louis College : [s.n.], 2020)
This paper focused on identifying and proposing solutions for the continual improvement needs for the Mariano Marcos State University- University Library System. To gather data, document review was carried out using Reports on Accreditation Survey Visits conducted by the Accrediting Agency of Chartered Colleges and Universities in the Philippines (AACCUP) from 2016 to 2019, as well as Focus Group Discussions to complement data gathered from the documents; especially in identifying the difference between AACCUP's recommendations and the findings of the study. The FGD involved a total of 15 participants: five (5) faculty members, seven (7) students, and three (3) librarians. A review of the documents revealed that, the AACCUP accrediting teams forwarded four (4) primary recommendations. Including the improvement of, planning, services, and facilities. In addition, analysis of the FGD generated (3) themes: co-creation preparation, collection production and management, and library modernization. Based on the findings, the researcher crafted and proposed Mariano Marcos State University Hybrid Library Project plan for the MMSU-Main Library's transformation into a hybrid library.
References: pages 99-107.
CHED-La Union
Keywords: Academic libraries